1996
DOI: 10.1093/infdis/173.5.1062
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of Human Cytomegalovirus by Human CD13-Specific Antibodies

Abstract: The mechanisms of inhibition of cytomegalovirus (CMV) infection by human CD13 (aminopeptidase N)-specific antibodies were studied. These antibodies protect CD13-negative and -positive cells from CMV infection only if incubated with the virus inoculum, suggesting they bind to CMV virions. The association of a CD13-like molecule with virions was further supported by the transfer of CD13 immunoreactivity to the surface of CD13-negative cells upon binding of CMV; the binding of CD13-specific antibodies directly to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…The host protein content of isolated HCMV particles was determined by searching for peptides detected by comparison with peptides predicted from a human-Fasta database. A total of 71 host cell proteins associated with HCMV virions were identified with high confidence, significantly increasing the number of previously identified virion proteins (Table 3; see also Table S1 in the supplemental material) (3,17,18,30,31,38,42). HCMV cellular virion proteins include cytoskeletal proteins, such as ␣-and ␤-actin, tubulin, several annexins, ␣-actinin, and vimentin, as well as cellular proteins involved in translational control, including initiation and elongation factors.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The host protein content of isolated HCMV particles was determined by searching for peptides detected by comparison with peptides predicted from a human-Fasta database. A total of 71 host cell proteins associated with HCMV virions were identified with high confidence, significantly increasing the number of previously identified virion proteins (Table 3; see also Table S1 in the supplemental material) (3,17,18,30,31,38,42). HCMV cellular virion proteins include cytoskeletal proteins, such as ␣-and ␤-actin, tubulin, several annexins, ␣-actinin, and vimentin, as well as cellular proteins involved in translational control, including initiation and elongation factors.…”
Section: Resultsmentioning
confidence: 93%
“…Previous studies have determined that there are about 30 to 35 viral proteins that compose HCMV virions (3,16). In addition to virally encoded structural proteins, a small number of cellular proteins, including CD13 (aminopeptidase N), ␤ 2 -microglobulin, protein phosphatase I, annexin II, and actin-related protein 2/3 (Arp2/ 3), have been shown to associate with the HCMV virion (3,17,18,30,38,42). The number of viral and cellular proteins that compose an infectious virion will always be controversial and dependent on the stringency of the isolation procedures.…”
mentioning
confidence: 99%
“…Similarly, since CD13 has been described to inactivate IL-8 [22], lL-8-induced effects could be shortened. Further more, CD 13 has been discussed to function as a corona virus receptor [23] or CD13-like molecules have been shown to be important in cytomegalovirus infection [24]; therefore, …”
Section: Discussionmentioning
confidence: 99%
“…Aminopeptidases are proteolytic enzymes that are involved in a wide range of functions, including digestion. Several reports have shown that aminopeptidases are also involved in defense responses (Delmas et al 1992;Pautot et al 1993;Giugni et al 1996), and aminopeptidase N from insect midguts is known to be involved in insecticide resistance. APNs also contain a putative Cry1A toxin-binding domain that is likely to be involved in determining affinity for Cry toxins (Nakanishi et al 2002).…”
Section: Genetic Mappingmentioning
confidence: 99%